ISIL’S EXTERNAL STRATEGY. PART 2 - Целуйко, М. Є. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The main directions and methods of ISIL’s external activity being implemented since chaliphateproclamation are examined in the article. General strategy and priority of activities at the externalterritories are defined based on each of eight publicly proclaimed wilayats (provinces) internalsituation. Expands ISILʼs policy on foreign territories and similarities and specific characteristics ofeach wilayat.